The Melanocortin System in Atlantic Salmon (Salmo salar L.) and Its Role in Appetite Control - Kalananthan, Tharmini; Lai, Floriana; Gomes, Ana S.; Murashita, Koji; Handeland, Sigurd; Rønnestad, Ivar (Frontiers in Neuroanatomy, 2020)
The melanocortin system is a key neuroendocrine network involved in the control of food intake and energy homeostasis in vertebrates. Within the hypothalamus, the system comprise two main distinct neuronal cell populations that express the neuropeptides proopiomelanocortin (POMC; anorexigenic) or agouti-related protein (AGRP; orexigenic). Both bind to the melanocortin-4 receptor (MC4R) in higher order neurons that controls both food intake and energy expenditure. This system is relatively well-conserved among vertebrates. However, in Atlantic salmon (Salmo salar L.), the salmonid-specific fourth round whole genome duplication lead to the presence of several paralogs genes which might result in divergent functions of the duplicated genes. In the current study, we report the first comprehensive comparative identification and characterization of Mc4r, and extend the knowledge of Pomc and Agrp in appetite control in Atlantic salmon. In silico analysis revealed multiple paralogs genes for mc4r (a1, a2, b1 and b2) in the Atlantic salmon genome, and confirmed the paralogs previously described for pomc (a1, a2 and b) and agrp (a1 and a2). All mc4r paralogs are relatively well-conserved with the human homolog, sharing at least 63% amino acid sequence identity. We analysed the mRNA expression of mc4r, pomc and agrp genes in 8 brain regions of Atlantic salmon post-smolt under 2 feeding states: normally fed and fasted for 4 days. The mc4ra2 and b1 mRNA were predominantly and equally abundant in the hypothalamus and telencephalon, the mc4rb2 in the hypothalamus and a1 in the telencephalon. All pomc genes were highly expressed in the pituitary, followed by hypothalamus and saccus vasculosus. The agrp genes showed a completely different expression pattern from each other, with prevalent expression of the agrp1 in the hypothalamus and agrp2 in the telencephalon. Fasting did not induce any significant changes in the mRNA level of mc4r, agrp or pomc paralogs in the hypothalamus or in other highly expressed regions between fed and fasted state. The identification and wide distribution of multiple paralogs of mc4r, pomc and agrp in Atlantic salmon brain provide new insights and give rise to new questions of the melanocortin system in the appetite regulation in Atlantic salmon.